A proinflammatory diet is associated with increased odds of frailty after 12-year follow-up in a cohort of adults. Issue 2 (24th September 2021) - Millar, Courtney L; Dufour, Alyssa B; Shivappa, Nitin; Habtemariam, Daniel; Murabito, Joanne M; Benjamin, Emelia J; Hebert, James R; Kiel, Douglas P; Hannan, Marian T; Sahni, Shivani
ABSTRACT: Background: Frailty occurs in 10–15% of community-living older adults and inflammation is a key determinant of frailty. Though diet is a modulator of inflammation, there are few prospective studies elucidating the role of diet-associated inflammation on frailty onset. Objectives: We sought to determine whether a proinflammatory diet was associated with increased odds of frailty in adults from the Framingham Heart Study (FHS). Design and Methods: This study was nested in a prospective cohort that included individuals without frailty. Diet was assessed in 1998–2001 using a valid FFQ, and frailty was measured in 2011–2014. FFQ-derived energy-adjusted dietary inflammatory index (E-DII®) scores were computed, with higher E-DII scores indicating a more proinflammatory diet. Frailty was defined as fulfilling ≥3 of 5 Fried Phenotype criteria. Information on potential mediators, serum IL-6 and C-reactive protein was obtained in 1998–2001. Logistic regression estimated ORs and 95% CIs for E-DII (as continuous and in quartiles) and frailty onset adjusting for relevant confounders. Results: Of 1701 individuals without frailty at baseline (mean ± SD age: 58 ± 8 y; range: 33–81 y; 55% female), 224 developed frailty (13% incidence) over ∼12 y. The mean ± SD E-DII score was −1.95 ± 2.20; range: −6.71 to +5.40. After adjusting for relevant confounders, a 1-unit higher E-DII score was associated with 16% increased odds of developing frailty (95% CI: 1.07, 1.25). In categorical analyses, participants in the highest (proinflammatory) compared with lowest quartile of E-DII had >2-fold increased odds of frailty (ORquartile4vs.1 : 2.22; 95% CI: 1.37, 3.60; P -trend < 0.01). IL-6 and C-reactive protein were not major contributors in the pathway. Conclusions: In this cohort of middle-aged and older adults, a proinflammatory diet was associated with increased odds of frailty over ∼12 y of follow-up. Trials designed to increase consumption of anti-inflammatory foods for frailty prevention are warranted.